The relationship between public and private bicycle use: the case of Seville - José I. Castillo-Manzano; Mercedes Castro-Nu\~no; Lourdes Lopez-Valpuesta (European Regional Science Association (ERSA), 2015)
Despite the success achieved by Public Bicycle Sharing Systems (PBSS) across the world, several researchers provide evidence on their limitations and constraints in a medium-long term, and bicycle ownership may be considered as a complementary tool to promote a 'bicycle-culture'. This paper aims to cover the gap about the interaction between both systems (public bicycle / private bicycle) and which are the key aspects to explain the bicycle-buying decision. After a fieldwork based on surveys conducted in Seville (Spain), one of the cities currently acknowledged worldwide for its successful policy of promoting cycling, we apply a Discrete Choice Model. Our findings show that among the socio-demographic factors that favor the move from the PBSS to the private bicycle are: having a higher level of education, being more progressive ideologically-speaking, and being a resident of the city itself; while age and gender do not appear to be conclusive. Experienced users, for whom the bicycle is a part of his /her healthy lifestyle, state a greater willingness to buy a bicycle. And the main obstacles to make the jump from the PBSS to the private bicycle, and that any action plan to support private bicycle usage should take into account, are: the lack of proper parking at the origin/destination, and fear of theft.
Keywords: R40; R42; 330; Public Bicycle Sharing System; Bicycle Ownership; Bicycle-buying decision